Two new clerodane-type diterpenoids from Bornean liverwort Gottschelia schizopleura and their cytotoxic activity - Ng, Shean Yeaw; Takashi Kamada; Monica Suleiman; Charles Santhanaraju Vairappan (2018)
The Bornean liverwort Gottschelia schizopleura was investigated phytochemically for the first time. Two new and four previously known clerodane-type diterpenoids were isolated from the MeOH extract of G. schizopleura through a series of chromatographic techniques. The structures of the new metabolites were established by analyses of their spectroscopic data (1D NMR, 2D NMR, HRESIMS and IR). All the isolated compounds 1–6 were tested against human promyelocytic leukaemia (HL-60), human colon adenocarcinoma (HT-29) and Mus musculus skin melanoma (B16-F10). Compound 1 and 2 showed active inhibition against HL-60 and B16-F10 cells.